Anti-interferon-γ autoantibody-associated disseminated Mycobacterium abscessus infection mimicking parotid cancer with multiple metastases: A case report. Issue 39 (September 2017) - Chang, Po-Hsiung; Chuang, Yu-Chung
Abstract: Rationale: Among the nontuberculous mycobacteria, Mycobacterium abscessus is a common cause of skin, soft tissue, and bone infections. However, disseminated M. abscessus infection that mimics cancer metastasis with an underlying relatively immunocompetent condition has rarely been reported. Patient concerns: A nonsmoking 73-year-old man with an underlying relatively immunocompetent condition reported a 2-month history of a mass in the region of his right parotid gland that had been steadily increasing in size. Diagnoses: The head and neck computed tomography showed an avidly enhancing tumor with central necrosis in the right parotid region and lymphadenopathy bilaterally at neck levels II–V (<6 cm) with a necrotic core. The radiologist and otolaryngologist both suspected a diagnosis of right parotid gland cancer with metastasis. Interventions: The necrotic tissue was removed surgically, and Mycobacterium culture showed M. abscessus . We collected a blood sample and detected anti-interferon-γ autoantibody. Outcomes: After 6 months of anti-M. abscessus treatment, physical examination showed remission of the parotid tumor, and axillary and supraclavicular lymphadenopathy. Lessons: We report a case of disseminated M. abscessus infection, which involved parotid glands with multiple lymphadenopathies in a person with an underlying relatively immunocompetent condition. Possible underlying mechanisms such as anti-interferon-γ autoantibody-associated immunodeficiency should be considered in a patient with disseminated M. abscessus infection without a known immunocompromised condition.